2008
DOI: 10.1007/s00049-008-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Hydrocarbons: Kairomones with a releaser effect in the sexual communication of the white-spotted longicorn beetle, Anoplophora malasiaca (Thomson) (Coleoptera: Cerambycidae)

Abstract: We conducted a series of experiments with the white-spotted longicorn beetle Anoplophora malasiaca (Thomson), and its host plant, Citrus unshiu, to examine the origin of the sesquiterpene hydrocarbons (SHCs; including b-elemene, b-caryophyllene, a-humulene, afarnesene, and several unidentified compounds) that are contained in the elytra of the beetles and act as an attractant. In the laboratory, mechanically wounded citrus branches, as well as those fed upon by A. malasiaca, attracted males more frequently tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 12 publications
2
37
1
1
Order By: Relevance
“…Males as well as females attract both sexes. The attractant is in volatiles derived from host Citrus unshiu (Yasui et al, 2007b(Yasui et al, , 2008. The role of host plant volatiles in A. malasiaca is discussed in detail in the following sections.…”
Section: Mate Location In Cerambycidaementioning
confidence: 99%
See 1 more Smart Citation
“…Males as well as females attract both sexes. The attractant is in volatiles derived from host Citrus unshiu (Yasui et al, 2007b(Yasui et al, , 2008. The role of host plant volatiles in A. malasiaca is discussed in detail in the following sections.…”
Section: Mate Location In Cerambycidaementioning
confidence: 99%
“…However, the mating systems of Monochamus alternatus endai (Fauziah et al, 1987;Kim et al, 1992), Xylotrechus pyrrhoderus (Iwabuchi, 1982(Iwabuchi, , 1985(Iwabuchi, , 1988Sakai et al, 1984;Iwabuchi et al, 1985Iwabuchi et al, , 1986, Psacothea hilaris (Fukaya and Honda, 1992, 1996aFukaya et al, 1996Fukaya et al, , 1997, and especially A. malasiaca have been examined in various contexts, and a comprehensive representation has emerged for these species. Host plant chemicals play a role for searching mates at long and short distances in A. malasiaca (Yasui et al, 2007b(Yasui et al, , 2008. There are complex chemicals for mate recognition as contact pheromone in A. malasiaca (Fukaya et al, 1999(Fukaya et al, , 2000Akino et al, 2001;Fukaya, 2003;Yasui et al, 2003Yasui et al, , 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…Freshly cut cocoa branches, such as those we evaluated, are still alive, and provide a large artificial source of damaged tissues emitting odors that could be attractants (kairomones) for S. breve adults. For example, sesquiterpene hydrocarbons, involved in the communication system of Anoplophora malasiaca at both long and short ranges, have been isolated from wounded host plants (Citrus unshiu) (Yasui et al, 2008;Yasui, 2009). Kairomones are often used by Cerambycidae as part of their communication system and have been used as bait to catch adult beetles regarded as agricultural pests, for example, Arhopalus tristis (Suckling et al, 2001), M. alternatus (Ikeda et al, 1980;Fan et al, 2007), Tetropium fuscum and T. castaneum (Sweeney et al, 2004(Sweeney et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…La técnica de SPME ha sido empleada principalmente para estudios en coleópteros (Said et al, 2003;Cai et al, 2007;Yasui et al, 2008;Arakaki et al, 2009), y recientemente para la identificación de sustancias emitidas por el tefrítido Anastrepha serpentina (Wiedemann) (Robacker et al, 2009). …”
Section: Búsqueda De Semioquímicosunclassified
“…SPME-gas chromatography (GC) was first applied in 1995 as an alternative method for the study of airborne insect pheromones (Malosse et al, 1995), and since then, SPME has been employed in sampling of insect volatiles, particularly in beetles (Said et al, 2003;Cai et al, 2007;Yasui et al, 2008;Arakaki et al, 2009). SPME has also been recently employed in the identification of chemicals emitted by Anastrepha serpentine (Robacker et al, 2009), but its use in medfly volatile collection has not yet been reported, as far as we know.…”
Section: Viii1 Introductionmentioning
confidence: 99%